Effects of propranolol and clonidine on brain edema, blood-brain barrier permeability, and endothelial glycocalyx disruption after fluid percussion brain injury in the rat. Issue 1 (January 2018) - Genét, Gustav Folmer; Bentzer, Peter; Hansen, Morten Bagge; Ostrowski, Sisse Rye; Johansson, Pär Ingemar
Abstract : BACKGROUND: Traumatic brain injury causes a disruption of the vascular endothelial glycocalyx layer that is associated with an overactivation of the sympathoadrenal system. We hypothesized that early and unselective beta-blockade with propranolol alone or in combination with the alfa2 -agonist clonidine would decrease brain edema, blood-brain barrier permeability, and glycocalyx disruption at 24 hours after trauma. METHODS: We subjected 53 adult male Sprague-Dawley rats to lateral fluid percussion brain injury and randomized infusion with propranolol (n = 16), propranolol + clonidine (n = 16), vehicle (n = 16), or sham (n = 5) for 24 hours. Primary outcome was brain water content at 24 hours. Secondary outcomes were blood-brain barrier permeability and plasma levels of syndecan-1 (glycocalyx disruption), cell damage (histone-complexed DNA fragments), epinephrine, norepinephrine, and animal motor function. RESULTS: We found no difference in brain water content (mean ± SD) between propranolol (80.8 ± 0.3%; 95% confidence interval [CI], 80.7–81.0) and vehicle (81.1 ± 0.6%; 95% CI, 80.8–81.4) ( p = 0.668) or between propranolol/clonidine (80.8 ± 0.3%; 95% CI, 80.7–81.0) and vehicle ( p = 0.555). We found no effect of propranolol and propranolol/clonidine on blood-brain barrier permeability and animal motor scores. Unexpectedly, propranolol and propranolol/clonidine caused an increase in epinephrine and syndecan-1 levels. CONCLUSION: This study does not provide any support for unselective beta-blockade with propranolol or the combination of propranolol and the alfa2 -agonist clonidine on brain water content. The novel finding of an increase in plasma concentrations of epinephrine and syndecan-1 after propranolol treatment in traumatic brain injury is of unclear significance and should be investigated further.